Spirits beyond Meaning - Scharf da Silva, Inga; Múscari, Marcello (Revista Brasileira de História das Religiões, 2021)
In this paper, we introduce the two German speaking Umbanda communities of the Casa St. Michael, House of Pure Water under the spiritual leadership of Mãe Gabriele and the Ilê Axé Oxum Abalô, Terra Sagrada under the spiritual guidance of Mãe Habiba and their placement in the European therapeutic scene as a way to explore the argument that beyond cultural adaptations and the correctness of symbolic content, a particularly Brazilian social experience is being transmitted to Europe in Umbanda rituals that lies beyond meaning. Its meaning is rather anchored in the very core of the ritual practice in its emphasis on marginalized figures and trance, reminding the European practitioners of the repressions of the colonial era und urge them to decolonize their thinking through Umbandist religious practice of the spirits of the Pretas Velhas and Pretos Velhos as spiritual personifications of old slaves and the Caboclas and Caboclos as indigenous spirits that evoke the collective trauma of violence against Africans and indigenous people in Brazil. As Umbanda triggers particular social experiences, we refer our insights on McLuhman’s argument that “the medium is the message”.